2005
DOI: 10.1038/sj.ejcn.1602241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E on the toxicity of oxidized LDL on endothelial cells in vitro in smokers vs nonsmokers on diets rich in fish

Abstract: Objective: To clarify whether supplementation of vitamin E can alter the low density lipoprotein (LDL) oxidation properties and thereby affect endothelial cell function and prostacyclin production in smokers compared to nonsmokers on diets rich in fish in a pilot study. Design: The LDL of six smokers and six nonsmokers on habitual high fish diet was isolated before and after an 8-week supplementation of vitamin E (800 IU/day). LDL was oxidized by incubation with CuSO 4 . Cytotoxicity of LDL oxidized to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…The increase in the lag phase for copper-induced LDL oxidation by antioxidants has already been described (Wen et al, 1999). Vitamin E, an endogenous antioxidant, is known to prevent LDL oxidation by donating the hydrogen atom of its phenolic hydroxyl group to a lipid peroxyl radical (Meydani, 1995;Seppo et al, 2005). Vigna et al (2003) showed that the increase in the lag phase and the reduction of the lipid peroxide formation are probably related to antioxidant properties or to mechanisms involving ion (Cu 2+ ) chelation.…”
Section: Discussionmentioning
confidence: 93%
“…The increase in the lag phase for copper-induced LDL oxidation by antioxidants has already been described (Wen et al, 1999). Vitamin E, an endogenous antioxidant, is known to prevent LDL oxidation by donating the hydrogen atom of its phenolic hydroxyl group to a lipid peroxyl radical (Meydani, 1995;Seppo et al, 2005). Vigna et al (2003) showed that the increase in the lag phase and the reduction of the lipid peroxide formation are probably related to antioxidant properties or to mechanisms involving ion (Cu 2+ ) chelation.…”
Section: Discussionmentioning
confidence: 93%
“…This might implicate oxLDL as a marker of acute vascular damage in smokers. Some previous intervention studies showed inconstancy in the changes of oxLDL and ICAM-1 in smokers,24,25) while more recently smoking intensity was reported to be associated with increased white blood cell count, but not C-reactive protein (CRP) levels, and smoking cessation did not reduce CRP. The relationship between CRP and smoking intensity might be masked by CRP's stronger relationship with adiposity 26)…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E works as an antioxidant, which prevents lowdensity lipoprotein-cholesterol (LDL-cholesterol) oxidation and subsequent damage to cell membranes, including the membranes of endothelial cells that line the blood vessels (Seppo, 2005). The vitamin works by donating a hydrogen atom from its phenolic hydroxyl group to a lipid peroxyl radical resulting in its conversion to a vitamin E radical.…”
Section: Epidemiological Studiesmentioning
confidence: 99%